Preface to the special issue on Monitoring and Modelling of Carbon-Balance-, Water- and Snow-Related Phenomena at Northern Latitudes - Aalto, Tuula; Peltoniemi, Mikko; Aurela, Mika; Böttcher, Kristin; Gao, Yao; Härkönen, Sanna; Härmä, Pekka; Kilkki, Juho; Kolari, Pasi; Laurila, Tuomas; Lehtonen, Aleksi; Manninen, Terhikki; et al. (Finnish Environment Institute, 2016)
Non peer reviewed